Prune-belly syndrome - Yenny Yenny; Kusuma P. A; Damanik M. P. (Indonesian Pediatric Society, 2009)
Prune-belly syndrome, also known as Eagle-Barretsyndrome, is a congenital anomaly comprisingthree clinical findings: deficient abdominalmusculature, urinary tract anomalies, andbilateral cryptorchidism. Other clinical findings involvingrespiratory, skeletal, digestion and cardiovascular systemmay also accompany the syndrome. The incidence isapproximately 1 : 30,000 to 40,000 live births and 95%of cases occur in boys. Pulmonary hypoplasia and kidneyfailure are important prognostic factors that contributeto 60% of mortality rate. Treatment includes surgicalcorrection of the abdominal wall and urinary tract,orchidopexy and other supportive managements.l-4 Wereport 4 cases on typical Prune-belly syndrome, togetherwith other clinical variants.